1991
DOI: 10.1016/0006-2952(91)90009-t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nisoldipine on recovery of coronary blood flow, sarcoplasmic reticulum function and other biochemical parameters in post-ischaemic porcine myocardium

Abstract: The effects of nisoldipine (0.1 micrograms/kg/min; n = 9) or its solvent (n = 9) were studied in pigs, in which left anterior descending coronary artery (LADCA) blood flow in both groups was reduced to 20% of baseline for 60 min and reperfused for 2 hr. Infusions were started at 30 min of ischaemia and lasted throughout reperfusion. In both groups, flow reduction abolished regional contractile function and caused similar decreases in the level of creatine phosphate (CP; by 70%) and the energy charge (from 0.91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, CCBs increase myocardial phosphocreatine and preserve adenosine triphosphate during ischemia (63). Nisoldipine significantly increases sarcoplasmic reticular intracellular calcium pump activity and slightly augments the rate of intracellular calcium uptake in post-ischemic myocardium (65).…”
Section: Ccbsmentioning
confidence: 99%
“…However, CCBs increase myocardial phosphocreatine and preserve adenosine triphosphate during ischemia (63). Nisoldipine significantly increases sarcoplasmic reticular intracellular calcium pump activity and slightly augments the rate of intracellular calcium uptake in post-ischemic myocardium (65).…”
Section: Ccbsmentioning
confidence: 99%
“…There is a good correlation between the enlargement of myocardial infarct size and the severity of reduction in regional myocardial blood flow during ischemia [17][18][19]. Because of the importance of this factor in affecting myocardial infarction, it is likely that differences in collateral blood flow between experimental subjects may contribute to the observed differences in the improvement in myocardial infarction.…”
Section: Discussionmentioning
confidence: 91%
“…Sassen et al (22) and Watts et al (18) suggested that the beneficial effect of nisoldipine was associated with in creased coronary flow during reperfusion, namely reduc tion in the no-reflow phenomenon. The present study also demonstrated that the cardioprotective effect of nisoldi pine was associated with the significant increase of coro nary flow during reperfusion under constant pressure perfu sion.…”
Section: Discussionmentioning
confidence: 99%